Evaluation of a paper by Guarnaccia et al. (2017) on the first report of Phyllosticta citricarpa in Europe. (23rd January 2018) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The Plant Health Panel reviewed the paper by Guarnaccia et al. (2017 ) and compared their findings with previous predictions on the establishment of Phyllosticta citricarpa . Four species of Phyllosticta were found by Guarnaccia et al. (2017 ) in Europe. P. citricarpa and P. capitalensis are well‐defined species, with P. citricarpa recorded for the first time in Europe, confirming predictions by Magarey et al. (2015 ) and EFSA (2008, 2014, 2016) that P. citricarpa can establish in some European citrus‐growing regions. Two new species P. paracitricarpa and P. paracapitalensis were also described, with P. paracitricarpa (found only in Greece) shown to be pathogenic on sweet orange fruits. Genotyping of the P. citricarpa isolates suggests at least two independent introductions, with the population in Portugal being different from that present in Malta and Italy. P. citricarpa and P. paracitricarpa were isolated only from leaf litter in backyards. However, since P. citricarpa does not infect or colonise dead leaves, the pathogen must have infected the above living leaves in citrus trees nearby. Guarnaccia et al. (2017 ) considered introduction to be a consequence of P. citricarpa having long been present or of illegal movement of planting material. In the Panel's view, the fruit pathway would be an equally or more likely origin. The authors did not report how surveys for citrus black spot (CBS) disease were carried out, therefore their claim that there was no CBS disease even where the pathogen was present is not supported by the results presented. From previous simulations, the locations where Guarnaccia et al. (2017 ) found P. citricarpa or P. paracitricarpa were conducive for P. citricarpa establishment, with number of simulated infection events by pycnidiospores comparable to sites of CBS occurrence outside Europe. Preliminary surveys by National Plant Protection Organisations (NPPOs) have not confirmed so far the findings by Guarnaccia et al. (2017 ) but monitoring is still ongoing.